Hubungan Locus Of Control Dengan Kepatuhan Pada Anggota Polisi Satuan Sabhara Di Polres X - Efa Kurniatih; Yuarini Wahyu Pertiwi; Ditta Febrieta (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Demonstration activities that often occur, many lead to riots in the form of destruction of facilities, congestion, and can even lead to clashes. Riots occur due to the presence of demonstrators and police officers who are in charge of securing demonstrations. The mass control force is one of the functions in the Bhayangkara samapta unit or SABHARA to secure every demonstration, so SABHARA needs to obey every applicable regulation, where obedience is related to locus of control. The purpose of this study was to determine the relationship between locus of control and obedience in police members of the SABHARA unit at X police station. The sampling technique used in this study was quota sampling by getting 85 respondents. The measuring instruments used are the obedience scale and the locus of control scale. The results of this study indicate the correlation coefficient value between obedience and internal locus of control of 0.320 with a significant level of 0.003 and on the variable of obedience and external locus of control of 0.141 with a significant level of 0.0198 p≤0.05, so it can be stated that there is no relationship between locus of control and obedience both in internal locus of control and external locus of control in police members of the SABHARA unit at X police station.